Historical knowledge : in quest of theory, method and evidence - Fellman, Susanna; Rahikainen, Marjatta (Cambridge Scholars Pub., 2012)
Historical Knowledge approaches the topic of historical knowledge in depth and from various angles. It seeks to offer theoretical and methodological building blocks for the use of anyone pursuing historical research. This book brings novel insights into classic and topical issues currently under debate: the importance of theory in historical thinking, the dialectic of "text" and "annotation", the actor and observer levels, the relationship between the general and the individual, the issue of ...